(untitled) (Confluenţe Bibliologice, 2018)
The author describes the participation of Balti librarians in the English Language Courses for Librarians (ESP) organized at the Fundamental Library of the Belorusian State University in Minsk in the framework of the Erasmus+ Program, “, Library Network Support Services: modernising libraries in Armenia, Moldova and Belarus through library staff development and reforming libraries [LNSS],” The training was promoted by Professor Gerard Cullen and trainer Valeriya Racheeva, the representatives of the project, The Pyramid Group, in Germany.